Superfluidity of Light and Its Breakdown in Optical Mesh Lattices - Wimmer, Martin; Monika, Monika; Carusotto, Iacopo; Peschel, Ulf; Price, Hannah M. (Physical Review Letters, 2021)
Hydrodynamic phenomena can be observed with light thanks to the analogy between quantum gases and nonlinear optics. In this Letter, we report an experimental study of the superfluid-like properties of light in a ()-dimensional nonlinear optical mesh lattice, where the arrival time of optical pulses plays the role of a synthetic spatial dimension. A spatially narrow defect at rest is used to excite sound waves in the fluid of light and measure the sound speed. The critical velocity for superfluidity is probed by looking at the threshold in the deposited energy by a moving defect, above which the apparent superfluid behavior breaks down. Our observations establish optical mesh lattices as a promising platform to study fluids of light in novel regimes of interdisciplinary interest, including non-Hermitian and/or topological physics.
CRIS-Team Scopus Importer:2023-04-20